Investigation of MWCNT addition into poly-dimethylsiloxane-based coatings. (15th March 2016) - Koumoulos, E. P.; Parousis, Th.; Trompeta, A.-F. A.; Kartsonakis, I. A.; Charitidis, C. A.
Abstract : The purpose of this work is to investigate the effects on the properties of poly-dimethylsiloxane-based coatings with the incorporation of multi-walled carbon nanotubes (MWCNT). For this reason, two types of MWCNT were examined (pristine and functionalised with carboxyl groups). An optimised dispersion method was employed to synthesise coatings with different wt-% concentrations of CNT, using different solvents. The morphology of the nanocomposite coatings was studied under optical and scanning electron microscopy. Moreover, their hydrophobic/hydrophilic behaviour was investigated by contact angle measurements. Furthermore, nanoindentation and nanoscratch tests were conducted to evaluate the nanomechanical properties. The results revealed an optimal threshold concentration of 0.1 wt-% in CNT that combines both acceptable dispersibility and mechanical enhancement of the composite coating. It was proven that the increase in CNT content deteriorates the surface and mechanical properties of the coatings.